SOCIUM AND NATURE: HARMONY OR CONFLICT? - Česlovas Kalenda (Problemos, 1999)
The article developes an idea that the ecological situation of Earth’s inhabitants depends on the ambivalent contents of the man’s relationship with nature. Both pro-nature and anti-nature trends objectively emerge in this relationship in an open or hidden form, and the specific shape of their correlation determines the current condition of the "nature-society" system. It is the specific feature of the civilized mankind’s existence that its survival is determined not by the fight against nature - as it had been in the paleolite era - but rather by a peaceful coexistence of socium and nature.